Tailored Fabrication of Transferable and Hollow Weblike Titanium Dioxide Structures. Issue 1 (16th November 2016) - Hiltunen, Arto; Lahtonen, Kimmo; Saari, Jesse; Ojanperä, Anniina; Sarlin, Essi; Wondraczek, Holger; Efimov, Alexander; Kaunisto, Kimmo; Vivo, Paola; Maccato, Chiara; Barreca, Davide; Fardim, Pedro; et al.
Abstract: The preparation of weblike titanium dioxide thin films by atomic layer deposition on cellulose biotemplates is reported. The method produces a TiO2 web, which is flexible and transferable from the deposition substrate to that of the end application. Removal of the cellulose template by calcination converts the amorphous titania to crystalline anatase and gives the structure a hollow morphology. The TiO2 webs are thoroughly characterized using electron microscopy, X‐ray diffraction, and X‐ray photoelectron spectroscopy to give new insight into manufacturing of porous titanium dioxide structures by means of template‐based methods. Functionality and integrity of the TiO2 hollow weblike thin films were successfully confirmed by applying them as electrodes in dye‐sensitized solar cells. Abstract : Flexible films : Weblike titanium dioxide thin films are prepared by applying atomic layer deposition on porous cellulose biotemplates. The method allows the incorporation of flexibility, transferability, and hollow structures into the manufacture of porous semiconducting metal oxide thin films in one process (see figure). XPS reveals changes in the chemical composition of the structure after removal of the template.